Gambaran Mikroskopis Berbagai Organ Merpati yang Menunjukkan Gejala Tortikolis dan Identifikasi Virus Penyakit Tetelo Berdasarkan Uji Agar Gel Presipitasi - Dewandaru, Risang Aji; Santoso, Ferdinand Prayogo Cahyo; Sugiyono, Sugiyono; Wibowo, Michael Haryadi (Jurnal Veteriner; Vol 21 No 4 (2020), 2020)
This study aimed to determine the microscopic conditions of organs of pigeons that suffered from torticollis and identify the cause of disease in torticollis pigeons . Three pigeons showed torticollis symptoms were obtained as sample and marked as pigeon A, B and C, respectively. Isolation of pathogen with inoculation into embryonated pigeon eggs obtained from parents with no history of vaccination and not indicated ND. Identification of ND with agar gel precipitation (AGP) test. Observation of microscopical changes with histopathologic preparation using hematoxylin and eosin staining. Histopathological examination showed that pigeons was done severe neuritis vagus, trakheitis, pneumonia, air sacculitis, hepatitis, pankreatitis, nefritis, jejunoileitis, ileocolitis and orchitis. Perivascular cuffing found in brain. Degenerative changes found in the hepar and ren. Cardiac severe necrotic lesion, and depletion in white pulp area of spleen. Proventricular tissue showed flattening of mucosal epithelium, congestion lesions found in pulmonary tissue. The results of slow hemagglutination test of pigeon egg allantoic fluid, which tested for hemagglutination (HA) showed positive HA result with titers varying between 2, 32, and 64. Serological identification carried out with the AGP test on all culture samples against ND antiserum showing positive results of ND virus. Based on these dara, it can be concluded that the pigeons with symptoms of torticollis is caused by ND virus.